Application of hydrological models for agri-environmental management based on international and national experiences - Juhász, Csaba; Pregun, Csaba (Acta Agraria Debreceniensis, 2014)
The ecological restoration of surface water flows requires the use of complex GIS and hydrological models. The HEC -RAS and MIKE11 programs calculate the hydraulic characteristics of runoff using the geometry and bed resistance the of flows. The presentation of some possible applications made through an example of the Berettyó, which is an extremely regulated river. The river belongs to the meandering category by Parker's classification system, which uses the relationship of the slope-Froude number and the depth- width ratio. Three coefficient of the four determining factor (entrenchment ratio, slope of water level, width-depth ratio) also indicates a mediocre to high sinuosity, while the river regulations established nearly straight bed-line. The standard water flow rates and characteristics have been determined based on the modeled Froude and Reynolds numbers. The flow conditions shifted to the laminar type by the changed line drawing which is ecologically lower status. Based on the results the morphological and ecohydrological river rehabilitation is appropriate.